Effect of clinical features on antiseizure medication doses in patients with newly diagnosed epilepsy - Hersi, Hire; Peltola, Jukka; Raitanen, Jani; Saarinen, Jukka T. (Frontiers in Neurology, 2023)
Objectives: We evaluate the effect of distinct clinical features on anti-seizure medication (ASM) doses in seizure-free and not seizure-free patients aged ≥16 years with new-onset epilepsy.Materials & Methods: This study included 459 patients with a validated diagnosis of epilepsy. The most prescribed ASMs were oxcarbazepine (OXC; n=307) followed by valproic acid (VPA; n=115), carbamazepine (CBZ; n=81), and lamotrigine (LTG; n=67). The seizure freedom rate with first or subsequent ASM was 88.0%. A retrospective analysis of patient records was performed to determine any association between doses of ASMs and patient characteristics.The median OXC dose in seizure-free patients aged >60 was 600 mg compared to 900 mg in younger patients. When controlling for age but not in unadjusted model, the median dose of OXC was lower (300 mg, p=0.018) for seizure-free patients compared to not seizure-free patients, also the median dose of OXC was 300 mg lower among older patients aged >60 (p<0.001). The median OXC doses for males aged ≤60 years was 300 mg higher than for females >60 years (900mg vs. 600mg, p=0.021). The median dose of VPA was 400 mg higher in males than in females (p<0.001) and 400 mg higher in not seizure-free patients compared to seizure-free patients only when adjusting for sex (p<0.001). Higher median doses for CBZ were registered with FAS compared with FBTCS (difference in median doses 200 mg; p=0.017).Conclusions: Significant OXC dose differences were detected between age groups, whereas VPA dosing was different in males and females. Moreover, CBZ doses were dependent on some seizure types. These data allow for the individualization of the initial target dosing based on key clinical characteristics.